An empirical analysis of the impact of ESG on financial performance: the moderating role of digital transformation - Fu, Tao; Li, Jiangjun (Frontiers in Environmental Science, 2023)
Introduction: Environmental, social, and governance(ESG) considerations have become increasingly important in the financial market and serve as concrete manifestations of sustainable development within a sector. Most corporate leaders have adopted ESG concerns as an important strategy to enhance their financial performance. Therefore, this study investigated whether ESG affects corporate financial performance, and if this relationship is moderated by digital transformation. Method: We used A-share listed companies in China from 2015 to 2021 as samples to test this mechanism. Results: Regression analysis showed that ESG positively and significantly affects corporate financial performance, and digital transformation drives this promoting effect. Furthermore, we found that the positive effect of current ESG on financial performance in the lag period will gradually weaken. Specifically, the heterogeneity test results show that the enhancement effect of ESG on financial performance is significant for non-state-owned companies but insignificant for state-owned companies; the same is true for companies located in the eastern region compared with those in the midwestern region. Finally, the enhancement effect of ESG on the financial performance of polluting firms is stronger than that on non-polluting firms. Conclusion: These findings will be useful for firms and government departments in formulating relevant policies.